1995
DOI: 10.1126/science.270.5241.1475
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of SN 1993J

Abstract: Source and a laser-heating system s~milar to one reported prevousy [C S. Yooetal , Phys. Rev B 48. 15529 (1993)l The x-ray beam slze, 20 k m by 20 k m , was comparable to the slze of laser-heat~ng spot, which varied from 30 to 100 k m , dependng on the temperature (For the later pari of ths study, we reduced the sze of x-ray beam to 5 I l m by 20 k m by focusng the 75 I l m by 20 krn beam n the vertcal drecton with an x-ray focusng reflector ) Therefore. the temperature gradents could be large n both the r a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 22 publications
5
51
0
Order By: Relevance
“…The early discovery of hydrogen lines in its spectra (Fillipenko & Matheson 1993) classified this supernova as Type II. Marcaide and coauthors showed the radio emission to arise from a shelllike structure (Marcaide et al 1995a) that expands selfsimilarly (Marcaide et al 1995b), thus giving strong support to the SIM. Marcaide et al (1997) also reported on the deceleration of the expansion (m = 0.86 ± 0.02), and concluded that there is strong evidence for the circumstellar medium density profile to be of the form ρ cs ∝ r −s , with s = 1.66, in good agreement with previous modeling of radio observations (s = 1.5; Van Dyk et al 1994;Lundqvist 1994) and with the modeling of both radio and X-ray observations, which require 1.5 < ∼ s < ∼ 1.7 (Fransson et al 1996;hereafter FLC96).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The early discovery of hydrogen lines in its spectra (Fillipenko & Matheson 1993) classified this supernova as Type II. Marcaide and coauthors showed the radio emission to arise from a shelllike structure (Marcaide et al 1995a) that expands selfsimilarly (Marcaide et al 1995b), thus giving strong support to the SIM. Marcaide et al (1997) also reported on the deceleration of the expansion (m = 0.86 ± 0.02), and concluded that there is strong evidence for the circumstellar medium density profile to be of the form ρ cs ∝ r −s , with s = 1.66, in good agreement with previous modeling of radio observations (s = 1.5; Van Dyk et al 1994;Lundqvist 1994) and with the modeling of both radio and X-ray observations, which require 1.5 < ∼ s < ∼ 1.7 (Fransson et al 1996;hereafter FLC96).…”
Section: Introductionmentioning
confidence: 99%
“…In modeling the radio emission from SN 1993J, we take into account all available observational data: (i) the distance to SN1993J, D = 3.6 Mpc (Freedman et al 1994); (ii) the supernova explosion date, t exp = March 28.0, 1993 (Nomoto et al 1993;Podsiadlowski et al 1993;Bartunov et al 1994); (iii) the supernova deceleration parameter, m = 0.86 (Marcaide et al 1997); (iv) the width of the radio emitting shell, ∆R = 0.3 R shock (Marcaide et al 1995b(Marcaide et al , 1997; (v) the index of the circumstellar density material, s = 1.66 (Marcaide et al 1997). Finally, we assume (vi) the same external electron temperature profile as in FB98: T e (r) = max T 15 10 15 cm/r , 2 × 10 5 K , where T 15 is the electron temperature in the circumstellar medium at r = 10 15 cm, which in our model is equal to 1.7 × 10 6 K. The thermal electron density of the circumstellar medium (assumed to be fully ionized with abundances X = 0.73, Y = 0.23), is given by n cs = 1.…”
Section: Synchrotron Radio Emission From Sn 1993jmentioning
confidence: 99%
“…Early VLBI observations resulted in size measurements (Bartel et al 1993 ;Marcaide et al 1993Marcaide et al , 1994, determinations of the angular expansion velocity (Bartel et al 1994 ;Marcaide et al 1995a) and a 5% bound on any deviation from circular symmetry of the shape of the radio source from 30 to 91 days after shock breakout (Bartel et al 1994). To reconcile the apparent di †erences between the radio and the optical polarization results, Tran et al (1997) speculated that the explosion was asymmetric in the inner parts of the supernova but symmetric and isotropic in the outer envelope where the radio radiation originates.…”
Section: Introductionmentioning
confidence: 99%
“…Its profile was very broad (FWHM ≈ 17,000 km s −1 ; Figure 8) and had a relatively flat top, but with prominent peaks and valleys whose likely origin is Rayleigh-Taylor instabilities in the cool, dense shell of gas behind the reverse shock [64]. Radio VLBI measurements show that the ejecta are circularly symmetric, but with significant emission asymmetries [65], possibly consistent with the asymmetric Hα profile seen in some of the spectra [53]. Figure 8: In the top spectrum, which shows SN 1993J about 7 months after the explosion, Hα emission is very weak; the resemblance to spectra of SNe Ib is striking.…”
Section: Links Between Type II and Type Ib/ic Supernovaementioning
confidence: 99%